Oncolytic adenovirus shapes the ovarian tumor microenvironment for potent tumor-infiltrating lymphocyte tumor reactivity. Issue 1 (13th January 2020) - Santos, João Manuel; Heiniö, Camilla; Cervera-Carrascon, Victor; Quixabeira, Dafne C A; Siurala, Mikko; Havunen, Riikka; Butzow, Ralf; Zafar, Sadia; de Gruijl, Tanja; Lassus, Heini; Kanerva, Anna; Hemminki, Akseli
Abstract : Background: Ovarian cancers often contain significant numbers of tumor-infiltrating lymphocytes (TILs) that can be readily harnessed for adoptive T-cell therapy (ACT). However, the immunosuppressive ovarian tumor microenvironment and lack of tumor reactivity in TILs can limit the effectiveness of the therapy. We hypothesized that by using an oncolytic adenovirus (Ad5/3-E2F-D24-hTNFa-IRES-hIL2; TILT-123) to deliver tumor necrosis factor alpha (TNFa) and interleukin-2 (IL-2), we could counteract immunosuppression, and enhance antitumor TIL responses in ovarian cancer (OVCA). Methods: We established ex vivo tumor cultures freshly derived from patients with advanced OVCA and evaluated the effects of Ad5/3-E2F-D24-hTNFa-IRES-hIL2 or Ad5/3-E2F-D24 (the control virus without TNFa and IL-2) on TILs, cytokine response and tumor viability. Tumor reactivity was assessed by determining interferon gamma (IFNg) response of clinically relevant TILs towards autologous T-cell-depleted ex vivo tumor cultures pretreated with or without the aforementioned oncolytic adenoviruses. Results: Treatment of ex vivo tumor cultures with Ad5/3-E2F-D24-hTNFa-IRES-hIL2 caused a substantial rise in proinflammatory signals: increased secretion of IFNg, CXCL10, TNFa and IL-2, and concomitant activation of CD4+ and CD8+ TILs. Potent tumor reactivity was seen, as clinically relevant TIL secreted high levels of IFNg in response to autologous T-cell-depleted ovarian ex vivo tumor cultures treated with Ad5/3-E2F-D24-hTNFa-IRES-hIL2. This phenomenon was independent of PD-L1 expression in tumor cells, a factor that determined the variability of IFNg responses seen in different patient samples. Conclusions: Overall, oncolytic adenovirus Ad5/3-E2F-D24-hTNFa-IRES-hIL2 was able to rewire the ovarian tumor microenvironment to accommodate heightened antitumor TIL reactivity. Such effects may improve the clinical effectiveness of ACT with TILs in patients with advanced OVCA.